Dr. Annie Beasant and Gandhi: A Historical Perspective (1847-1933): The Influence of Dr. Annie Besant's Perspectives on Spiritual Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper manages the profound training with uncommon reference to Dr. Annie Besant's perspectives in which her life and social way of thinking just as Theosophical way of thinking impact profound instruction. The paper likewise manages her theosophical way of thinking dependent on the standards of 'The Unity of God' and of 'The Universal Brotherhood' which are the essential piece of otherworldly instruction. In this paper an endeavor has been made to perceive, understand, discover, break down, combine, assess and fundamentally inspect the prevailing variables answerable for reinforcing profound training with respect to Dr. Annie Besant's perspectives.